Iterated Discrete Hardy-Type Inequalities - Zhangabergenova, Nazerke; Temirkhanova, Ainur (Eurasian Mathematical Journal, 2023)
In this paper, we discuss new discrete inequalities of Hardy-type involving iterated operators. Under some conditions on weight sequences, we establish necessary and sufficient conditions for the validity of these inequalities.